Outcome and Feasibility after 7 Years of Therapeutic Hypothermia in Southern Brazil - Procianoy, Renato S.; Corso, Andrea L.; Schoenardie, Bruna O.; de Oliveira, Georgia P.F.; Longo, Maria G.; Silveira, Rita C. (American Journal of Perinatology, 2020)
Objective This study aimed to describe the experience with a protocol of therapeutic hypothermia (TH) in southern Brazil.Study Design Newborns with gestational age > 35 weeks with evidence of perinatal asphyxia plus moderate or severe encephalopathy were recruited between March 2011 and November 2017. Whole-body hypothermia for 72 hours, starting within the first 6 hours of life was used. Survivors underwent magnetic resonance imaging (MRI) and electroencephalogram (EEG). The primary outcome was death during hospitalization and neurodevelopment assessed using the Bayley Scales of Infant Development III (BSID III) at 12 months of age.Results A total of 72 newborns were treated (41 with moderate encephalopathy and 31 with severe encephalopathy), of whom 16 died. MRI was performed in 56 patients, and 24 presented some alterations. Fifty-three patients had an EEG: 11 normal, 20 mildly altered, 12 moderately altered, and 10 severely altered. Forty patients were evaluated through BSID III: 45% presented with some delay in neurodevelopment, 8 (20%) had motor retardation, 15 (37.5%) had language delay, and 13 (32.5%) had a delay in cognitive development.Conclusion Mortality and adverse events were similar to those described in large randomized controlled trials. TH is a safe and an effective method of neurologic protection in asphyxiated newborns in a developing country when performed adequately.
Keywords: hypoxic–ischemic encephalopathy; therapeutic hypothermia; perinatal asphyxia; neurodevelopment